A Study on Designing Video Tutorials for Promoting Security Features: A Case Study in the Context of Two-Factor Authentication (2FA). Issue 11 (2nd November 2017) - Albayram, Yusuf; Khan, Mohammad Maifi Hasan; Fagan, Michael
ABSTRACT: This article investigates the effectiveness of informational videos that are designed to provide an introduction to two-step verification (i.e., 2FA) and in turn seeks to improve the adoption rate of 2FA among users. Toward that, eight video tutorials based on three themes (e.g., Risk, Self-efficacy, and Contingency) were designed, and a three-way between-group study with 399 participants on Amazon's MTurk was conducted. Furthermore, a follow-up study was run to see the changes in participants' behavior (e.g., enabling of 2FA). The Self-efficacy and Risk themes were found to be the most effective in making the videos more interesting, informative, and useful. Willingness to try 2FA was found to be higher for participants who were exposed to both the Risk and Self-efficacy themes. Participants' decisions regarding actually enabling 2FA was found to be significantly correlated with how interesting, informative, and useful the videos were. Implications of our findings in a broader context are discussed in the article.